Recovery Timescales of the Dayside Martian Magnetosphere to IMF Variability. Issue 20 (30th October 2019) - Romanelli, N.; DiBraccio, G.; Modolo, R.; Leblanc, F.; Espley, J.; Gruesbeck, J.; Halekas, J.; Mcfadden, J.; Jakosky, B.
Abstract: In this work we revisit an event observed by Mars Atmosphere and Volatile Evolution MissioN in the solar wind where the interplanetary magnetic field (IMF) rotates around the Mars‐Sun axis during ∼6 min. Based on a time‐dependent LATMOS Hybrid Simulation, we determine recovery timescales of the dayside Martian magnetosphere normalized by the IMF variability timescale. Particularly, we find that such recovery timescales range between 8 s and 11 min for an ∼90° IMF rotation that lasted 50 s (observed as part of the 6‐min time interval), depending on the considered magnetospheric region. We also find that the O + plume recovery timescales range between 40 and 120 s, taking greater values for further downstream distances (at least up to 1 R M downstream from the terminator plane). This range is on the order of the magnetosheath O + gyroperiod, showing the kinetic nature of the plume recovery process. Key Points: Hybrid numerical simulation results are used to estimate recovery timescales of the dayside Martian magnetosphere to IMF variability Recovery timescales of the dayside magnetosphere range between 8 s and 11 min for a 50‐s IMF rotation, depending on the considered region O + plume recovery timescales increase in the downstream direction (up to 1 R M from the terminator) and are close to the sheath O + gyroperiod